A STUDY TO ASSESS THE RESPIRATORY IMPAIRMENTS AMONG THREE WHEELER AUTO TAXI DRIVERS: Life Science-Physiology - PRAMANIK, PURUSHOTTAM; NARAYAN GANGULI, INDRA; CHOWDHURY, ARCHANA; GHOSH, BASUDEB (International Journal of Life Science and Pharma Research, 2013)
Transportation is the major culprit of air pollution and lungs are more susceptible to it. Auto taxi drivers are exposed to harmful chemicals and toxic substances from their vehicle-exhausts through inhalation. The purpose of the present study was to evaluate pulmonary functions of auto drivers by means of spirometry. The present study was carried out on 96 three wheeler auto taxi drivers of Chinsurah town in Hooghly,a southern district of West Bengal in India and compared it with 90 healthy male residing in the same geographical area those are not occupationally exposed to automobile exhaust. The pulmonary function test (PFT) variables were Forced Vital Capacity ( FVC ), Forced Expiratory Volume in 1second (FEV1), Ratio of FEV1 and FVC, Peak Expiratory Flow Rate (PEFR) and Forced Expiratory Flow 25-75% (FEF25-75%). All subjects were divided into smokers and nonsmokers. PFT results showed significant low value of pulmonary function indices including forced vital capacity (FVC), forced vital capacity in the first second (FEV1), forced expiratory flow 25-75% (FEF25-75%) and peak expiratory flow rate (PEFR) compared with control group subjects (p<0.05 to p<0.001 ) except %FEV1/FVC (p>0.05).The restrictive type pulmonary impairment was found in smokers and nonsmokers study subjects. Obstructive and mixed type of pulmonary impairment were noted in smokers study subjects. In conclusion we can assume that petrol engine emission from auto taxi causes respiratory impairment to its drivers. There was higher percentage of respiratory impairment in smoker-drivers than nonsmoker ones in our study.